2000
DOI: 10.1021/ma990021h
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of Ultrathin Supported Diblock Copolymer Films:  Theory and Experiment

Abstract: An analysis of the morphological behavior of substrate-supported diblock copolymer films for thicknesses t below the equilibrium period L 0 of the copolymer is presented. Substrate-supported films generally exhibit dissimilar interactions between the copolymer block components and the free and substrate surfaces. Accordingly, in this study, self-consistent-field calculations that incorporate asymmetric surface energetics were used to assess equilibrium film morphologies. Phase diagrams were constructed as a fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

24
238
0
2

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 223 publications
(264 citation statements)
references
References 56 publications
24
238
0
2
Order By: Relevance
“…At a thickness of 19 nm, almost all of the PI surface domains form uniform dots surrounded by the PS matrix (Fig 1c). Drawing on the structures reported for PS-b-PLMA films, which was called a hybrid structure, 39 we propose that the PS surface shown here in The PI component has a strong interaction with the Si substrate and a lower surface free energy compared with the PS component. 29 Therefore, we expect that in thicker films the PI will wet the Si substrate and also create a wetting layer at the free surface to minimize the total interfacial free energy when in an equilibrium state.…”
Section: Preparation Of Copolymer Templatesmentioning
confidence: 68%
“…At a thickness of 19 nm, almost all of the PI surface domains form uniform dots surrounded by the PS matrix (Fig 1c). Drawing on the structures reported for PS-b-PLMA films, which was called a hybrid structure, 39 we propose that the PS surface shown here in The PI component has a strong interaction with the Si substrate and a lower surface free energy compared with the PS component. 29 Therefore, we expect that in thicker films the PI will wet the Si substrate and also create a wetting layer at the free surface to minimize the total interfacial free energy when in an equilibrium state.…”
Section: Preparation Of Copolymer Templatesmentioning
confidence: 68%
“…46 The confinement effect on block copolymers is a significant topic in the nanoscale characterization of polymer materials. One-dimensional (in thin films) 47 or two-dimensional (in porous materials) 48 confinement effects on microphaseseparated structures of block copolymers have been extensively studied both theoretically and experimentally, however there are few experimental studies of three-dimensional confinement systems. Ozin and Manners showed that lamellar layers of poly(styrene-block-ferrocenylethylmethylsilane) align along the spherically confined spaces in the inverse opal templates of silica.…”
Section: Block Copolymersmentioning
confidence: 99%
“…Similarly, in the macroscopic drop region, domain orientation may be expected to be random and macroscopic viscosity remains isotropic. Hence, the domain structure may be accounted for via a macroscopic viscosity so that general spreading dynamics still follows the Tanner's law (4).…”
Section: Spreading Of Homopolymer Filmsmentioning
confidence: 99%
“…Equilibrium structure of block copolymer systems was in the center of theoretical and experimental research for a number of years now, and is mostly understood 2,3,4,5,6,7,8,9 . It is known that in the bulk, at temperatures below order-disorder transition (ODT), molten diblock copolymers phase-separate into periodic structures with periodicity dependent on polymer size.…”
Section: Introductionmentioning
confidence: 99%